Evaluasi Pengalaman Pengguna Terhadap Fitur Sistem Informasi Akademik Dengan Metode Kano (Studi Kasus : Mahasiswa Filkom UB) - Nila Ayu Rosyidah; Diah Priharsari; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Student Academic Information System of Brawijaya University (SIAM UB) is a system provided by Brawijaya University which functions to help student services in academic matters. A system that is said to be good if it can meet user needs to increase user satisfaction. The purpose of this research is to determine the decent experiences and bad experiences of users and the classification of features that affect the level of gratification and disappointment based on user perceptions. The method used in this research is the interview method and the Kano method. The interview method is obtained to explore the experience of using SIAM features. The Kano method is obtained to categorize the features into categories in the Kano Model. Namely Attractive, Indifferent, Must Be, One Dimensional, Reverse and Questionable. After grouping the features, the calculation of increases and decreases to the level of user satisfaction with each feature is carried out using Better and Worse. Informants taken in the interview method were 13 respondents, the number was retrieved based on saturation data and the collection was conducted by snowball sampling. Meanwhile, for the Kano method as many as 98 respondents by distributing to students of the UB Faculty of Computer Science. The results of the interview method were the decent experiences that many respondents felt because SIAM helped meet the needs of academic services, and the bad experiences felt by many respondents because they often experienced server downs. The result of the Kano method is that the student entrepreneurial data feature is in the Indifferent category, the attendance feature and fast track registration are in the Attractive category, the rest is in the One Dimensional category. Feature that has the highest Better and Worse scores is the recap feature of study results that is included in the One Dimensional category and the lowest is the student entrepreneurial data feature that is included in the Indefferent category.